Threat and efficacy in Malaysia’s cancer news coverage - Collin, Jerome; Ting, Su Hie (PiscoMed Publishing Pte Ltd, 2017)
The news media plays important roles not only in creating and disseminating health messages, but also in influencing people’s perceptions of health and their health behaviours. However, much more needs to be known about the creation process, particularly how health messages are created with the goal of raising awareness and knowledge, and changing people’s attitudes and behaviours. This paper presents a study aimed at examining cancer risk messages in Malaysia’s leading newspapers. Methods: Our search identified count the total 73 articles related to cancer which were published in three leading Malaysian English dailies in 2012 – September 2017. Of these, 10 were selected for a content analysis using the Extended Parallel Process (EPPM) Model. The analysis focused on the presence and the levels of two important components required for designing effective health risk message: threat (severity and susceptibility) and efficacy (responses efficacy and self-efficacy). The language used in the news articles was also analysed to see whether it helped enhance the threat-efficacy levels which are crucial for increasing message acceptance and yielding behaviour change. Results: Present study shows that the varying presence of threat and efficacy in the articles as evidenced by messages that focused on threat alone with no efficacy and messages that highlighted both threat and efficacy. Results also show contrasting levels of threat and efficacy as evidenced by messages that possessed high levels of threat and efficacy and messages that revealed a high level of threat and a low level of efficacy. Furthermore, the contents were composed differently in terms of language use: some articles used neutral language while others used vivid and descriptive language in addressing the topic and target audience. These have implication on message acceptance and behaviour change where high levels of threat and efficacy, and the ways in which vivid, descriptive and intense language enhance those levels, not only increase people’s reception of messages, but also and their willingness to change their behaviour. Conclusion: The findings of this study hold important implications for news agencies to consider combining threat and efficacy and using language skilfully and persuasively to create effective cancer risk messages. This work was supported by the Transdisciplinary Research Grant Scheme (TRGS) of the Ministry of Higher Education awarded to the researchers at Universiti Malaysia Sarawak: C09/TRGS/1519/2016.